Cognitive and preference disparities of Chinese consumers regarding the disclosure of unsafe food recall information - Taiping Li; Xiaohui Jin; Daocai Zhu (Frontiers in Public Health)
IntroductionInformation disclosure is important in promoting unsafe food recalls and reducing potential food safety risks. However, the governance of unsafe food recall information in China is distorted, leading to cognitive dissonance in Chinese consumers’ perceptions of unsafe food recall information. Focusing on consumers’ search and cognitive costs, this study suggests that market regulators should proactively and fully disclose unsafe food recall information to satisfy consumers’ needs and preferences for recall information, thereby optimizing consumer perceptions and facilitating the improvement of the information governance system for unsafe food recalls.MethodsThis study administered a survey via a discrete choice experiment to obtain data from 1,010 consumers in China and employed multiple linear regression (MLR) to analyze the overall cognition and preferences of consumers regarding food recall information and identify differences in cognition and preferences regarding unsafe food recall information.ResultsChinese consumers experience cognitive dissonance regarding food recall information, and their utility can be improved through disclosure. They expressed preferences for recall information about food shops and distribution markets, more visualized hazard content, and new media presentations. Those who had purchased unsafe food, families with pregnant women or children, and those with more education were more concerned about recall information. Consumers’ information preferences also show a bystander mentality; however, consumers with higher educational levels are more altruistic.DiscussionThe results suggest that personalized, intuitive, and cognitively matched recall information can reduce consumers’ search and cognitive costs and increase their utility. This finding provides a reference and practical basis for establishing a food safety information governance system in China.